2005
DOI: 10.1021/ma0501489
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Shape-Memory Polymer Networks:  Characterization with Solid-State NMR

Abstract: Polymer networks made from oligo[(l-lactide-ran-glycolide)]dimethacrylates by UV curing are characterized by solid-state NMR. These polymer networks show a shape-memory effect and could be used as temporary implant materials for medical applications. The 13C spectra enable the direct determination of the cross-link density by a signal at 44 ppm. This is used to correlate its intensity with the chain segment length as well as to study the kinetics of photo-cross-linking. The latter is compared with the gel cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…It has been reported that a high glassy modulus correlates with high shape fixity during simultaneous cooling and unloading, and elasticity ratios above 100 allow for greater resistance to deformation and better shape recovery. 13 According to these findings, material with cure step 1 at 258C should exhibit less shape recovery than the others, since the elastic ratio is 53 while other elastic ratios are above 100.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that a high glassy modulus correlates with high shape fixity during simultaneous cooling and unloading, and elasticity ratios above 100 allow for greater resistance to deformation and better shape recovery. 13 According to these findings, material with cure step 1 at 258C should exhibit less shape recovery than the others, since the elastic ratio is 53 while other elastic ratios are above 100.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 95%
“…In addition, their surface can readily be modified for biocompatibility and drug elution. 12,13 Thermomechanical behavior and shape memory properties have been reported for SMP materials made from polyurethanes, 1,2,14-17 ethylene-vinyl acetate copolymers, 18 oligo(e-caprolactones), 19 poly(ethylene glycol), and poly(ethylene terephthalates). 20 The shape memory effect of thermal SMPs resides in the structure of the polymer, which is often described as being a two phase structure comprised of a hard, or fixing phase, and a soft, or reversible phase.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking usually brings further benefits with, such as high recovery stress and rate compared to the linear counterparts. The group of Lendlein functionalized oligomers composed of L-lactide and glycolide with UV-curable methacrylate end groups [17]. The comonomer ratio and length of the chain segments in the corresponding polymer (PLLA-GA) were varied in the experiments.…”
Section: Molecular Structure 211 T G -Based Systemsmentioning
confidence: 99%
“…While other classes of thermally activated shape memory materials have been developed, shape memory alloys (SMA) [2] and shape memory ceramics [3] being the two other major classes [4], SMPs have a number of unique and promising properties. Specifically, in the field of medicine, research into the development of new SMP with adjustable modulus [5], greater strain recovery, an adjustable actuation temperature, and the option of bioresorption [1,6] has opened the possibility for new medical devices and applications.…”
Section: Introductionmentioning
confidence: 99%